Enhancing teacher well-being through cognitive behavioral theory and visual imagery-based writing with the resulting tower model - Chaemyoung Lee; Soo Eun Chae (Scientific Reports)
Abstract Educators in South Korea face significant challenges such as job dissatisfaction and increased workloads. This qualitative study evaluated the efficacy of a visual imagery-based online writing program designed to enhance teachers’ psychological well-being and stress management based on Cognitive Behavioral Theory. Conducted from October to December 2020, the study involved ten middle school teachers from Y City, Gyeonggi-do. Using in-depth interviews, the research focused on the psychological impacts of the program, particularly in the areas of self-reflection and stress management, while introducing the “Tower Model” for self-therapy. Findings revealed substantial improvements in self-reflection, emotional understanding, and authenticity among participants. The writing exercises provided critical insights into personal and psychological well-being, thereby enhancing mental health. The “Tower Model” proved effective in improving self-understanding, stress management, and resilience. The model integrates emotional expression and rational observation, guiding participants toward a balanced self-reflection process. Six key themes were identified: Self-Understanding, Understanding Others, Confrontation, Positivity, Organization, Future Design, collectively contributing to increased self-awareness and optimism. This study highlights the potential of visual imagery-based online writing coupled with mindfulness practices as an effective tool for supporting teachers’ psychological well-being. However, the small sample size and short duration limit generalizability, and further research is recommended to explore its broader applicability across diverse and culturally sensitive contexts.